A Comparative Study of Environmental Indoor Radon and Thoron in Shahjahanpur and Hardoi District of Central Uttar Pradesh - Anil Kumar1, Indu Singh1, V.K. Bhatt 1 and R. Singh2, R.B.S. Rawat1, (Recent Research in Science and Technology, 2011)
The measurement of indoor radon, thoron and their daughter products was carried out in about fifty houses of dist. Shahjahanpur and Hardoi of Central Uttar Pradesh, India using LR-115 plastic track detectors. The measurements were made in residential houses from June 2008 to May 2009 hanging twin cup radon dosimeter at a height of 1.5-2m from ground level. The twin cup radon dosimeter can record the values of radon, thoron and their decay products separately. The graphs were plotted for radon concentration versus number of houses, thoron concentration versus number of houses and dose rate versus number of houses for different seasons. The resulting dose rates due to radon, thoron varied from 0.04 to 1.46 µSv/h. The observed radon and thoron concentration inside the houses of central Uttar Pradesh were found to be lower than the ICRP recommended value of 200 Bqm-3 and thus are within safe limits.